The Iran revolution and its influence on the revival of Islam - Potočnik, Dragan (Annales. Series historia et sociologia, 2018)
The Iranian revolution presents a milestone in the history of the Islamic world as it created the fi rst Islamic state. Despite the fact that the revolution occurred in Shia Iran, it also reverberated in the Sunni world and infl uenced the internal political development in many Arab countries by inspiring Islamic activism. Before the revolution, it had been obvious for quite some time that secular Arab nationalism had failed in protecting Muslims against foreign invasions. The revolution had a strong infl uence on Sunni fundamentalists, encouraging them to organize mass movements. The Iranian revolution, however, did not have an ideological impact on the Sunni Muslims, as they viewed it as a project which had the purpose of strengthening Shiism in the Muslim world at the expense of Sunnism. The revolution thus did not solve the problems within the Islamic world, nor did it help to improve the relationship between the West and the Islamic world.
Keywords: Homeini; Iran; Islamic civilisation; islamska civilizacija; preporod Islama; revolucije; revolutions; Shiism; suniti; Sunnism; šiiti